Low-temperature rapid synthesis of high-stable carbon dots and its application in biochemical sensing. (April 2020) - Long, Caicheng; Qing, Taiping; Fu, Qing; Jiang, Zixin; Xu, Jin; Zhang, Peng; Feng, Bo
Abstract: Carbon dots (CDs) have wide applications in chemical sensor, electrocatalysis, and photocatalysis, but most preparations of carbon dots need high temperature and long reaction time. In this work, a chemical oxidation and surface passivation approach was introduced to synthesize fluorescent CDs in low-temperature condition using phosphoric acid and ammonium hydroxide as the oxidant and passivator, respectively. The as-prepared CDs exhibited two emission bands at 356 nm and 440 nm with different excited wavelengths, and high quantum yield (25.51%). More important, the fluorescent CDs display good water-solubility and high biocompatibility even under broad pH range or high ionic strengths. Moreover, this high-stable fluorescent CDs was also employed as a ratiometric fluorescence probe for ascorbic acid sensing based on the inner filter effect (IFE) between ascorbic acid and CDs. This strategy represented excellent sensitivity and selectivity for ascorbic acid analysis both in buffer and biological samples, providing a valuable platform for ascorbic acid detection in clinic diagnosis. Graphical abstract: Schematic presentation of high-stable carbon dots (CDs) synthesis via chemical oxidation and surface passivation in low-temperature (80 °C). This excellent CDs was employed as a ratiometric fluorescence probe for ascorbic acid detection due to the inner filter effect between ascorbic acid and CDs. Image 1 Highlights: High-stable CDs were synthesized by chemical oxidation and surface passivation in low-temperature condition. The as-prepared CDs exhibit excellent fluorescent stability even under broad pH range or high ionic strengths. The fluorescent CDs was employed as a ratiometric fluorescence probe for ascorbic acid sensing.